2011
DOI: 10.1128/aac.00691-10
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Origins and Spread of Sulfadoxine-Resistant Plasmodium falciparum dhps Alleles in Thailand

Abstract: The emergence and spread of drug-resistant Plasmodium falciparum have been a major impediment for the control of malaria worldwide. Earlier studies have shown that similar to chloroquine (CQ) resistance, high levels of pyrimethamine resistance in P. falciparum originated independently 4 to 5 times globally, including one origin at the Thailand-Cambodia border. In this study we describe the origins and spread of sulfadoxineresistance-conferring dihydropteroate synthase (dhps) alleles in Thailand. The dhps mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 47 publications
10
39
1
Order By: Relevance
“…Previous molecular evolutionary study had shown that only two lineages of high sulfadoxine resistance (parasites harboring three or four substitutions in DHPS) were observed in Cambodia (38). These two lineages were also found in Thailand (40). A large-scale study in Africa has shown that only five resistant lineages were observed in mild-to moderate-resistant parasites (parasites harboring one or two substitutions in DHPS) (69).…”
Section: -3 Sulfadoxinementioning
confidence: 98%
See 2 more Smart Citations
“…Previous molecular evolutionary study had shown that only two lineages of high sulfadoxine resistance (parasites harboring three or four substitutions in DHPS) were observed in Cambodia (38). These two lineages were also found in Thailand (40). A large-scale study in Africa has shown that only five resistant lineages were observed in mild-to moderate-resistant parasites (parasites harboring one or two substitutions in DHPS) (69).…”
Section: -3 Sulfadoxinementioning
confidence: 98%
“…An Ala-to-Gly substitution at position 437 (encoding DHPS with amino acid sequences SGKAA at positions 436, 437, 540, 581, and 613, where the altered residue is underlined) has been proposed as the first step to sulfadoxine resistance (13,38,39). Triple-mutant DHPS enzymes (AGEAA, SGEGA, and SGNGA) demonstrate the highest levels of sulfadoxine resistance in the natural parasite populations, and parasites encoding quadruple-mutant DHPS enzymes have been detected (at rare frequencies) in some places in Southeast Asia (13,38,40).…”
Section: -2 Pyrimethamine and Sulfadoxinementioning
confidence: 99%
See 1 more Smart Citation
“…In South America, there is a prevalence of the triple mutant SGEGA allele (16). Triple mutant alleles AGEAA and SGEGA, along with novel triple mutant allele SGNGA, are prevalent in Thailand and Cambodia (4,33). In India, the prevalence of different mutant dhps alleles varies from region to region (1,3,11), due to different rates of malaria transmission and level of drug resistance (10).…”
mentioning
confidence: 99%
“…Molecular tools that can detect resistant alleles have been useful in population-based studies in tracking resistant parasites in countries where malaria is endemic. The detection of molecular markers of resistance has historically involved various PCR-based genotyping methods, such as sequence-specific PCR amplification, pyrosequencing, and Sanger sequencing of a genomic region containing one or more resistance mutations (1)(2)(3)(4). One major limitation of these conventional genotyping methods is their detection limit of minor allele frequencies (MAFs).…”
mentioning
confidence: 99%